Grenada : 2007 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2008)
The 2007 Article IV Consultation with Grenada discusses strong economic rebound in the aftermath of a hurricane devastation and broadly favorable economic prospects, with major tourism investments under way and the gradual recovery of the agricultural sector. The government's highly successful debt restructuring is now largely complete and has resulted in substantial debt service savings. Executive Directors welcomed the efforts being made by the authorities to enhance the business climate and improve competitiveness, including through the recently developed national export strategy and other measures to reduce business costs.